STANDAR KOMPETENSI GURU DALAM PERSPEKTIF PENDIDIKAN ISLAM: Volume 1, Nomor 1 (2024) - Ratna Desta; Nur Widiastuti; Ratika Novianti (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2024)
In this modern era, many people work as teachers, but many teachers do not understand what competencies an educator must have. There are even teachers who have been certified and obtained certify ation allowances but have not seriously prepared and carried out their duties as teachers professionally. The lack of competencepossessed by Islamic religious education teachers affects the results of the learning that will be received by students. Based on the results of the competency data analysis, according , the competency data teachers must have, which consists of: Pedagogic Competence, Personality Competence, Social Competence and Professional Competence. Of the four competences that must be possessed by Islamic Religious Education teachers, they must be based on the Al-Qur’an and Hadith. Abuddin Nata also emphasized that as a teacher of Islamic Religious Education, in addition to having four competencies, he must also have a prophetic mission, self-purification, develop knowledge continuously while getting closer to Allah.